113k views
2 votes
Solve the system of equations using substitution -3x + 2y = 12 x = 2y - 8

User Schmurfy
by
4.5k points

1 Answer

6 votes

Answer:

(-2, 3)

Explanation:

Given the system of equations:

-3x + 2y = 12

x = 2y - 8

You can 'substitute' the expression '2y - 8' for the value of 'x' in the first equation and solve for 'y':

-3(2y - 8) + 2y = 12

Distribute: -6y + 24 + 2y = 12

Combine like terms: -4y + 24 = 12

Subtract 24 from both sides: -4y + 24 - 24 = 12 - 24 or -4y = -12

Divide both sides by -4: -4y/-4 = -12/-4 or y = 3

Use y = 3 to solve for 'x':

x = 2(3) - 8 or 6 - 8

x = -2

(-2, 3)

User YeJiabin
by
4.9k points